The effect of probiotic nutrition of Saccharomyces boulardii and Saccharomyces cerevisiae on yield, antioxidant activity and expression of interleukin-6 gene in Holstein calves - Sabooni, S.; Chamani, M.; Sadeghi, A. A.; Amin-Afshar, M.; Kashan, N. E. J. (Diponegoro University, 2020)
An experiment was performed to investigate the probiotic effect of Saccharomyces boulardii and Saccharomyces cerevisiae on yield, antioxidant activity, and expression of interleukin-6 gene in Holstein calves. Sixteen calves were divided into 4 dietary treatments with 4 calves/treatment. Experimental treatment diets include 1) control (without probiotic use), 2) milk soluble probiotics based on S. boulardii (1 g/kg), 3) milk soluble probiotics based on S. cerevisiae (1 g/kg) and 4) A mixture of yeast probiotics S. boulardii and S. cerevisiae as a solution in dairy milk (1 g/kg each). The completely randomized design was used in this experiment. The results showed that feeding S. boulardii and S. cerevisiae did not have a significant effect on performance traits compared with control. There was no significant difference between the different treatments for the number of antioxidant enzymes compared to the controls. Superoxide dismutase (SOD) in the treatments used probiotics were higher than the control. The expression of interleukin-6 gene expression was increased significantly (P<0.05) for treatments 3 and 4 on Days 10, 30 and 60 compared to the control. In conclusion, addition of probiotics did not alter performance traits of antioxidant activity, but the S. cerevisaetreatment did increase interleukin-6 gene expression which suggests an effect on the immune system.